Déjà vu: Stimulating open drug discovery for SARS-CoV-2. Issue 5 (May 2020) - Ekins, Sean; Mottin, Melina; Ramos, Paulo R.P.S.; Sousa, Bruna K.P.; Neves, Bruno Junior; Foil, Daniel H.; Zorn, Kimberley M.; Braga, Rodolpho C.; Coffee, Megan; Southan, Christopher; Puhl, Ana C.; Andrade, Carolina Horta
Highlights: We describe our prior efforts in open drug discovery for Ebola and Zika virus. We summarize the current literature for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). We detail computational repurposing efforts and results for SARS-CoV-2. To be prepared for future outbreaks we argue we need novel broad-spectrum antivirals. Limitations of these efforts include funding for experimental validation, and this lags behind the computational work. Abstract : In the past decade we have seen two major Ebola virus outbreaks in Africa, the Zika virus in Brazil and the Americas and the current pandemic of coronavirus disease (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). There is a strong sense of déjà vu because there are still no effective treatments. In the COVID-19 pandemic, despite being a new virus, there are already drugs suggested as active in in vitro assays that are being repurposed in clinical trials. Promising SARS-CoV-2 viral targets and computational approaches are described and discussed. Here, we propose, based on open antiviral drug discovery approaches for previous outbreaks, that there could still be gaps in our approach to drug discovery.